2017
DOI: 10.1016/j.biopsycho.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of evoked phantom limb sensations

Abstract: HighlightsWe present a neural network related to evoked phantom sensations in amputees.Such networks were not related to the stimulation from the residual limb.Difference in intra- and inter-hemispheric interactions between amputees and yoked controls.This finding yields novel insights into the neural basis of phantom sensation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 53 publications
2
21
0
2
Order By: Relevance
“…In line with a previous study (Andoh et al., 2017), we could evoke phantom sensations and even PLP by nonpainful electrical stimulation at the residual limb in amputees with chronic PLP. PLP has been shown to be temporally reduced after blocking peripheral inputs by injecting lidocaine in amputees with PLP (Buch et al., 2019; Vaso et al., 2014).…”
Section: Discussionsupporting
confidence: 92%
“…In line with a previous study (Andoh et al., 2017), we could evoke phantom sensations and even PLP by nonpainful electrical stimulation at the residual limb in amputees with chronic PLP. PLP has been shown to be temporally reduced after blocking peripheral inputs by injecting lidocaine in amputees with PLP (Buch et al., 2019; Vaso et al., 2014).…”
Section: Discussionsupporting
confidence: 92%
“…As mentioned above, it was found that people who experience worse PLP also show a greater shift of their lower face representation towards the missing hand cortex ( Flor et al., 1995 ). A similar association was never established for non-painful phantom sensations, which have been in turn linked with frontal and parietal activity ( Andoh et al., 2017 ). The finding of a positive association between S1 remapping and PLP has been replicated using multiple paradigms and participant groups ( Diers et al., 2010 ; Lotze et al., 1999 ; MacIver et al., 2008 ).…”
Section: Altered Body Representation Following Arm Amputationmentioning
confidence: 56%
“…The co-occurrence of these post-amputation sensations suggest that they may share neural mechanisms with PLP [ 48 ]. An fMRI study by Andoh et al showed that inducing non-painful phantom sensations in people with amputations activated the somatosensory and premotor cortices contralateral to the amputated limb [ 69 ]. The activation of similar cortical areas has been recorded in patients with PLP upon induction of their PLP [ 70 74 ].…”
Section: Discussionmentioning
confidence: 99%